Simulation Process of Injection Molding and Optimization for Automobile Instrument Parameter in Embedded System. (30th August 2021) - Ramesh, S.; Nirmala, P.; Ramkumar, G.; Sahoo, Satyajeet; Anitha, G.; Gnanasekar, A. K.; Isaac JoshuaRamesh Lalvani, J.
Abstract : The automobile instrument is the indispensable item that is essential to keep the driver conversant of the process of the engineer and the other system. There are different parameters involved in the automobile instrument, which requires a different process involved in creating the automobile parameter. This research is designed to show the simulation development of injection molding and optimization of automobile instrument parameters using different optimization techniques. In this paper, Taguchi Orthogonal parameter design and particle swarm optimization (PSO) are used to measure the shrinkage volume rate and warpage amount rate. Most of the studies are designed to calculate the reduction and warpage for the gate location and glass material. The Taguchi orthogonal design contains five different parameters which are inversely proportional to each other. Hence, by optimizing those parameters, the injection molding procedure is passed out. In this research, the paper is designed to process the injection molding for the automobile instrument parameter using optimization techniques.